2019
DOI: 10.3389/fimmu.2019.02968
|View full text |Cite
|
Sign up to set email alerts
|

Update on Fc-Mediated Antibody Functions Against HIV-1 Beyond Neutralization

Abstract: Antibodies (Abs) are the major component of the humoral immune response and a key player in vaccination. The precise Ab-mediated inhibitory mechanisms leading to in vivo protection against HIV have not been elucidated. In addition to the desired viral capture and neutralizing Ab functions, complex Ab-dependent mechanisms that involve engaging immune effector cells to clear infected host cells, immune complexes, and opsonized virus have been proposed as being relevant. These inhibitory mechanisms involve Fc-med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(54 citation statements)
references
References 201 publications
(218 reference statements)
1
50
0
Order By: Relevance
“…How close antigens are to each other, as well as their individual size and shape, could influence how Fc domains are presented as well as the level of avidity experienced ( Figure 11A). There is some evidence to suggest that where an antibody binds on antigen may influence innate effector activity for HIV (261), influenza (262,263) and Ebola viruses (104,264), among other examples, but there is not yet convincing molecular data to provide a general model that ties these observations together.…”
Section: Reconciling Antibody-antigen and Antibody-fcγr Structuresmentioning
confidence: 99%
“…How close antigens are to each other, as well as their individual size and shape, could influence how Fc domains are presented as well as the level of avidity experienced ( Figure 11A). There is some evidence to suggest that where an antibody binds on antigen may influence innate effector activity for HIV (261), influenza (262,263) and Ebola viruses (104,264), among other examples, but there is not yet convincing molecular data to provide a general model that ties these observations together.…”
Section: Reconciling Antibody-antigen and Antibody-fcγr Structuresmentioning
confidence: 99%
“…This is in contrast to fields where vaccines are used to treat infectious disease. In these contexts, it is well-acknowledged that antibody subclass plays an active role in controlling viral infections (66)(67)(68). One posited role for this effect is the engagement of additional activating Fc Receptors in myeloid cell populations (56).…”
Section: Discussionmentioning
confidence: 99%
“…The cross-linkage among the antigen, antibody and the effector cells triggers immune effector functions, including antibody-dependent cellular cytotoxicity (ADCC), antibody-dependent cell-mediated phagocytosis (ADCP) and complement-dependent cytotoxicity (CDC), which contribute to the clearance of virus-infected cells and virus particles (ADCP particularly) ( Figure 2 C). Many sources of evidence have shown that effector functions mediated by antibodies are critical for protection against influenza virus, human immunodeficiency virus and respiratory syncytial virus [ 117 , 118 , 119 ]. In addition, ADCC antibodies are associated with the clinical presentation of neonatal herpes simplex virus (HSV) infection [ 120 ] and are protective against HSV-1 and -2 in a mouse model of maternal immunization [ 121 ].…”
Section: Mda Interference: a Major Bottleneck For Ndv-vectored Vacmentioning
confidence: 99%